Managing The COVID-19 Pandemic: Health and Food Security of Rohingya Refugees at Kutopalong Camp, Cox's Bazar, Bangladesh - Raudatul Zanah AS; M Hanif Abiyyu Handana (Jurnal Sentris, 2022)
Research on "Managing The COVID-19 Pandemic: Health and Food Security of Rohingya Refugees in Kutopalong Camp, Cox's Bazar, Bangladesh" is a recent study that seeks to explain the managing of COVID-19 from both the Bangladesh government and international organizations to Rohingya refugees in the Kutopalong Camp, Cox's Bazar, which focuses on health security and food security. This study seeks to provide a new, more realistic approach on how Rohingya refugees are handled in Kutopalong Camp during COVID-19 and when COVID-19 ends, of co,urse, by incorporating the concept of health security and food security as the theoretical basis of research. The discussion of this research was obtained using qualitative methods as well as comparing with previous research.